The negative effects of haram money on the national economy with reference to Iraq (Journal of the College of Basic Education, 2022)
The research included several main axes, in the forefront of which was the definition of forbidden money linguistically and legally. Then I built the most important sources of forbidden money resulting from the crimes of theft, smuggling, trafficking in taboos, usury, burglary, usurpation, prostitution, drug trafficking and abuse of office, to other means of forbidden earning. It is fraudulent and unlawful money that is not lawful for its owner